Moving from fun, humour and enjoyment - Lea Alexandra Gunnarsdóttir 2002- (2024)
In this essay, I will theorize the effect fun, humour and enjoyment have on a creative process and how it can impact the performers and audience. The essay is written in relation to my final piece Töfrandi Kvöld, a musical that involved magic, which was made as my final piece of my BA education in contemporary dance from the Iceland University of the Arts. With this project, I wanted to analyse what happens when you utilize fun, humour and entertainment in a creative process. How does it affect the participant's experience of the process? I will use psychological theories by Alice Isen, as well as theorize the “pleasure activism” by adrienne marie browns and look at Mette Ingvartsen's “Yes Manifesto.” I will also research the biological effects that positive emotions have. Through what I discovered, while working on the project as well as this research essay, I came to the conclusion that fun, humour and enjoyment as a driving force can create a less stressful and more enjoyable atmosphere for the participants of the project which resulted in an enjoyable experience for both the performers and audience.